Penyesuaian Dusun Jangka Panjang Ditinjau dari Resiliensi Komunitas Pasca Gempa - Novianty, Anita (Faculty of Psychology, Universitas Gadjah Mada, 2011)
Disasters always occur without can be predicted precisely. The need to use community's strengths are very important component in new disaster-risk reduction effort. This study aims to find out the correlation between community resilience on long-termed community coping post-earthquake of May 26, 2006. Predictor variable in this study is community resilience, andthe criterium variable is long-termed community coping. The instruments used in this study consisted of Community Coping Scale is modification of the Community Well-Being Scaledeveloped by (Prawitasari et al., 2009; Prawitasari, 2011), and Community Resilience Scale developed by Researcher. This research was held in the earthquake affected areas in Klaten.Data were collected from 60 respondents (34 males and 26 females); age ranges from15-78 years old. Reliability test with Alpha Cronbach indicates both instruments were reliable(αCCS=0.930; αCRS=0.925). This study hypothesized that there is a correlation between community resilience and long-termed community coping post-earthquake. Pearson-ProductMoment Correlation Analysis was used to analyze the data. Result shows that there is a positive correlation between community resilience and long-termed community coping post-earthquake (r = 0.571, p < 0.05).